Elongational experiments on polymer melts and their assessment - Münstedt, Helmut (AIP Conference Proceedings, 2013)
Regarding the literature, steady-state values of the elongational viscosity are not widely documented and it is still an open question, whether the time-dependent elongational viscosity of strain-hardening polymeric materials runs through a maximum as a function of time before it reaches its steady state. For the assessment of molecular theories reliable experimental data are essential, however. From a survey of extensional experiments at constant elongational rates it becomes very probable that an extended stationary state of elongational exists and that maxima of the tensile stresses or even overshoot phenomena are due to non-uniform deformations of the samples. This conclusion is supported by creep experiments for which a steady state is reached at comparatively smaller total elongations corresponding to a better uniformity. © 2013 AIP Publishing LLC.
Created from Fastlane, Scopus look-up
Keywords: Experimental devices; Extensional rheology; Polymer melts; Steady-state elongational viscosity; Theories; Uniformity of deformation